INFORMATION TECHNOLOGIES FOR MANAGING AVIATION SYSTEMS - Lutskyi, Maxim; Khrashchevskyi, Rimvidas; Ivanets, Olga; Nesterenko, Kateryna (Science-based technologies, 2022)
The proposed work analyzes the peculiarities of implementing a proactive approach in aviation. Within the framework of this approach, the human factor is considered as the cause of the occurrence of a dangerous event. An analysis of decision-making features was carried out to determine the possibilities of increasing the reliability of decision-making in aviation. The probability of occurrence of a dangerous event, the trigger of which is the human factor, is proposed to be determined based on the assessment of the functional state of the operator based on the information parameters of the cardiovascular system. The paper proposes an approach to determining the informativeness of parameters that directly depend on the number of measurements of these parameters. It is proposed to increase the reliability of decision-making regarding the state of the object not by increasing the number of measurements, but by additional processing of already measured information parameters, i.e. obtaining secondary information. As an example, the results of measurements of the RR intervals of the electrocardiogram by methods of nonlinear dynamics, namely Poincaré maps, were processed. The use of nonlinear dynamics methods to the already measured parameters of the cardiovascular system can provide an increase in the amount of information about the state of the operator and provide a new understanding of changes in the parameters of the cardiovascular system in hidden physiological states, providing additional prognostic information and complementing the traditional analysis in the time and frequency domains. The methods of nonlinear dynamics provide additional and independent information about the physiological, as well as about the hidden physiological response to the destabilizing factors. In the paper, as an example for processing already existing informational parameters of RR intervals of the electrocardiogram, their projection in phase space was carried out using Poincre maps to increase the informativeness of heart rate variability ṘR intervals are presented as a time series, and a Poincaré map allows the estimation of heartbeat dynamics based on a simplified phase space embedding. The use of Poincaré maps, as one of the methods of nonlinear dynamics, allows qualitative and quantitative analysis of cardiac signals, which reflects data variability. The “3D Poincaré map” obtained in the work have an advantage in the implementation of their construction and can be used to illustrate such properties as non-stationarity and multistability, which are important for understanding the dynamics of the physiological regulation system in the presence of destabilizing factors. In addition, it is possible to reveal unexpected regularities in the structure of the data, which makes this method useful for research studies, simplifying the formation of hypotheses, the development and verification of mathematical/physiological models.